ANALISIS KAJIAN TERORISME DAN RADIKALISME DALAM 3 PERSPEKTIF TEORITIS - Frisca Alexandra (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
Terrorism and radicalism have been a global threat since the United States declared war on terrorism in 2001. Since then, no country in the world has escaped the threat of terrorism. Terrorism itself not only happens because of radical understanding but also because of the threat to sense of identity. The threat to this sense of identity is often responded by a radical-minded person or group of people using open violence. The threat to sense of identity according to Johan Galtung is included in cultural violence, where if cultural violence continues to get ignored it will appear open acts of violence. The countries of the world continue to cope with the threat of terrorism and radicalism, both through the hard approach and soft approach, which both approaches the perpetrators of terrorism itself while referring to the triangle of the Galtung’s conflict, there are other approaches that can be done to prevent radicalism and terrorism namely by overcoming cultural violence and creating tolerant society conditions amid identity heterogeneity.Keywords: Terorism, Radicalism, Identity, Cultural Violence